OTCPicks.com: OTCPicks.com Daily Market Movers Digest Midday Report for Thursday, August 28th IBOT, DMAT, GLCC, SEED, WEHI, CEGE (M2 Presswire, 2008)
As of June 30, 2008 and September 30, 2007, Origin's balance sheet included cash and cash equivalents of RMB 334.66 million (US$48.79 million) and RMB162.31 million (US$21.66 million), respectively. Investments in US Government Agency bonds amounted to RMB 12.57 million (US$1.83 million) and RMB 133.97 million (US$17.88 million), respectively. Net working capital amounted to RMB 285.96 million (US$ 41.69 million) and RMB 294.98 million (US$39.37 million), respectively. Total shareholders' equity increased to RMB 332.38 million (US$48.46 million) as compared to RMB 296.92 million (US$39.63 million) for September 30, 2007. To date, VITAL-2 enrolled 408 patients. The IDMC based its recommendation on 114 deaths of which 67 occurred in the GVAX plus Taxotere combination treatment arm and 47 deaths occurred in the Taxotere control arm. At this time, a specific cause for the imbalance in deaths has not been identified and the IDMC reported no new safety issues for GVAX when administered in combination with Taxotere. The Company plans to fully analyze the clinical data from these patients to attempt to understand the potential cause for the higher rate of deaths observed in the GVAX immunotherapy plus Taxotere combination arm, including an assessment of potential imbalances between the two arms of the study such as baseline characteristics and prognostic factors, as well as other treatment variables. In light of the IDMC's observation with respect to VITAL-2, the Company has requested that the IDMC perform a previously unspecified futility analysis of VITAL-1, the other Phase 3 clinical trial of GVAX immunotherapy for prostate cancer. The Company expects the results of the VITAL-1 futility analysis in approximately one month. Release of Liability: Through use of this website viewing or using you agree to hold OTCPicks.com, its operators owners and employees harmless and to completely release them from any and all liability due to any and all loss (monetary or otherwise), damage (monetary or otherwise), or injury (monetary or otherwise) that you may incur. Neither the information presented nor any statement or expression of opinion, or any other matter herein, directly or indirectly constitutes a representation by the publisher nor a solicitation of the purchase or sale of any securities. OTCPicks.com is being compensated up to eight thousand dollars by a third party for IBOT advertising and promotional services. For a complete list of disclosures go to http://www.otcpicks.com/disclosure-details.htm. The information contained herein is based on sources which we believe to be reliable but is not guaranteed by us as being accurate and does not purport to be a complete statement or summary of the available data. The owner, publisher, editor and their associates are not responsible for errors and omissions. They may from time to time have a position in the securities mentioned herein and may increase or decrease such positions without notice. Any opinions expressed are subject to change without notice. OTCPicks.com encourages readers and investors to supplement the information in these reports with independent research and other professional advice. All information on featured companies is provided by the companies profiled, or is available from public sources and OTCPicks.com makes no representations, warranties or guarantees as to the accuracy or completeness of the disclosure by the profiled companies or the information contained herein. OTCPicks.com and its affiliates are not registered investment advisors or a broker dealers. OTCPicks.com has been advised that the investments in companies profiled are considered to be high risk and use of the information provided is at the investor's sole risk. OTCPicks.com also advises that the purchase of such high risk securities may result in the loss of some or all of the investment. Investors should not rely solely on the information presented. Rather, investors should use the information provided by the profiled companies as a starting point for doing additional independent research on the profiled companies in order to allow the investor to form his or her own opinion regarding investing in the profiled companies. Factual statements made by the profiled companies are made as of the date stated and are subject to change without notice. Investing in micro-cap securities is highly speculative and carries an extremely high degree of risk. It is possible that an investor's entire investment may be lost or impaired due to the speculative nature of the companies profiled. OTCPicks.com makes no recommendation that the securities of the companies profiled should be purchased, sold or held by individuals or entities that learn of the profiled companies through OTCPicks.com. OTCPicks.com owners may or may not hold positions in the companies that are profiled.